Performance of the CORDEX‐Africa regional climate simulations in representing the hydrological cycle of the Niger River basin. Issue 24 (22nd December 2015) - Mascaro, Giuseppe; White, Dave D.; Westerhoff, Paul; Bliss, Nadya
Abstract: The water resources of the Niger River basin (NRB) in West Africa are crucial to support the socioeconomic development of nine countries. In this study, we compared and evaluated performances of simulations at 0.44° resolution of several regional climate models (RCMs) of the Coordinated Regional climate Downscaling Experiment (CORDEX) in reproducing the statistical properties of the hydrological cycle of the NRB in the current climate. To capture the large range of climatic zones in the region, analyses were conducted by spatially averaging the water balance components in four nested subbasins. Most RCMs overestimate (order of +10% to +400%, depending on model and subbasin) the mean annual difference between precipitation ( P ) and evaporation ( E ), whose observed value was assumed equal to the long‐term discharge based on the mass conservation principle. This is due to a tendency to simulate larger mean annual P and a weak hydrological cycle in the E channel. Some exceptions appear in the humid most‐upstream subbasin, where a few RCMs underestimate P . Overall, the representation of the water balance is mostly sensitive to the parameterized land surface and atmospheric processes of the nested RCMs, with less influence of the driving general circulation model. This finding is supported by further analyses on seasonal cycle and spatial variability of the water balance components and on model performances in reproducing observed climatology. Results of this work should be considered when RCMs are used directly or in impact studies to develop policies and plan investments aimed at ensuring water sustainability in the NRB. Key Points: Water balance components of CORDEX RCMs evaluated in the Niger River basin Most RCMs overestimate runoff at four subbasins Representation of water balance is mostly sensitive to RCMs, with less influence of GCM